Barriers to women's participation in public procurement in Africa: Empirical evidence from Uganda. - BC, Basheka (INTERNATIONAL JOURNAL OF SOCIAL SCIENCES AND HUMANITY STUDIES, 2020)
Global policy agendas and declarations continue to focus on the participation of women and women-owned businesses (WOBs) in the public and private sectors. The United Nations (UN) Sustainable Development Goals (SDGs) have compelled countries to adopt affirmative action (AA) strategies to ensure equal opportunities for women and men. The World Bank (2005) highlights that women constitute approximately 70% of Uganda’s labour force, yet most are employed in the informal sector. Basheka’s (2018b) research on Uganda’s inclusive public procurement opportunities, barriers, and strategies to female entrepreneurs’ participation in public procurement in Uganda substantiated these findings. In this regard, Basheka (2018b) highlights that removing gender inequality is key to economic growth and eradicating poverty. Like many African countries, Uganda faces several challenges regarding women’s participation in government procurement. In line with this, this paper focuses on women’s participation in Uganda’s public procurement system. To help address this issue, the authors present a framework to support the participation of women and WOBs in Uganda’s public procurement system. The framework was based on an empirical analysis of the barriers that women face regarding Uganda’s public procurement processes. The study collected primary and secondary information using corresponding data-collection and -analysis techniques. Interviews were conducted with key informants within Uganda’s central and local government, and surveys were administered to various WOBs. Capacity, finance, information, and legal and regulation-related aspects were identified as the four key obstacles to participating in this potentially lucrative process. It is recommended that the Ugandan government establish an appropriate legal and regulatory framework supported by top-level commitment to ensure that WOBs have access to national and international trading opportunities